Enhanced intra-articular therapy for rheumatoid arthritis using click-crosslinked hyaluronic acid hydrogels loaded with toll-like receptor antagonizing peptides - Lee, Soyeon; Seo, Jiyoung; Kim, Young Hun; Ju, Hyeon Jin; Kim, Shina; Ji, Yun Bae; Lee, Hai Bang; Kim, Han Su; Choi, Sangdun; Kim, Moon Suk (Acta Biomaterialia, 2023)
Rheumatoid arthritis (RA) is a chronic inflammatory disorder that results in the deterioration of joint cartilage and bone. Toll-like receptor 4 (TLR4) has been pinpointed as a key factor in RA-related inflammation. While Toll-like receptor antagonizing peptide 2 (TAP2) holds potential as an anti-inflammatory agent, its in vivo degradation rate hinders its efficacy. We engineered depots of TAP2 encapsulated in click-crosslinked hyaluronic acid (TAP2+Cx-HA) for intra-articular administration, aiming to enhance the effectiveness of TAP2 as an anti-inflammatory agent within the joint cavity. Our data demonstrated that FI-TAP2+Cx-HA achieves a longer retention time in the joint cavity compared to FI-TAP2 alone. Mechanistically, we found that TAP2 interacts with TLR4 on the cell membranes of inflammatory cells, thereby inhibiting the nuclear translocation of NF-κB and maintaining it in an inactive cytoplasmic state. In a rat model of RA, the TAP2+Cx-HA formulation effectively downregulated the inflammatory cytokines TNF-α and IL-6, while upregulating the anti-inflammatory cytokine IL-10 and the therapeutic protein 14-3-3ζ. This led to a more rapid restoration of cartilage thickness, increased deposition of glycosaminoglycans, and new bone tissue formation in the regenerated cartilage, in comparison to a single TAP2 treatment after a six-week period. Our results suggest that TAP2+Cx-HA could serve as a potent intra-articular treatment for RA, offering both symptomatic relief and promoting cartilage regeneration. This innovative delivery system holds significant promise for improving the management of RA and other inflammatory joint conditions. Statement of significance: In this study, we developed a therapy by creating toll-like receptor 4 (TLR4)-antagonizing peptide (TAP2)-loaded click-crosslinked hyaluronic acid (TAP2+Cx-HA) depots for direct intra-articular injection. Our study demonstrates that FI-TAP2+Cx-HA exhibits a more than threefold longer lifetime in the joint cavity compared to FI-TAP2 alone. Furthermore, we found that TAP2 binds to TLR4 and masks the nuclear localization signals of NF-κB, leading to its sequestration in an inactive state in the cytoplasm. In a rat model of RA, TAP2+Cx-HA effectively suppresses inflammatory molecules, specifically TNF–α and IL-6, while upregulating the anti-inflammatory cytokine IL-10 and the therapeutic protein 14-3-3ζ. This resulted in faster regeneration of cartilage thickness, increased glycosaminoglycan deposits in the regenerated cartilage, and a twofold increase in new bone tissue formation compared to a single TAP2 treatment.
Keywords: Anti-inflammatory agents; Click-crosslinking hyaluronic acid depot; Crosslinked; Inflammatory cytokines; Intra-articular injection; Prolonged release; Rheumatoid arthritis; Toll-like receptor 4; Toll-like receptor-antagonizing peptide; Toll-like receptors; 14-3-3 Proteins; Animals; Anti-Inflammatory Agents; Arthritis, Rheumatoid; Cartilage, Articular; Cytokines; Glycosaminoglycans; Hyaluronic Acid; Hydrogels; Injections, Intra-Articular; Interleukin-10; Interleukin-6; NF-kappa B; Peptides; Rats; Toll-Like Receptor 4; Toll-Like Receptors; Tumor Necrosis Factor-alpha; Click-crosslinking hyaluronic acid depot; Intra-articular injection; Prolonged release; Rheumatoid arthritis; Toll-like receptors-antagonizing peptide